The Brazilian species of the family Aristeidae Wood-Mason (Crustacea: Decapoda) - D'Incao, Fernando (1998)
The Brazilian Aristeidae are reviewed and shown to be represented by the following species: Aristaeomorpha foliacea (Risso, 1827); Hepomadus tener Smith, 1884; Plesiopenaeus edwardsianus {Johnson, 1867); Benthesicymus bartletti Smith, 1882; Gennadas brevirostris Bouvier, 1905; and Bentheogennema intermedia (Bate, 1888). Of these, A. foliacea, H. tener, B. bartletti and G. brevirostris are new records for Brazil. All of the species are widely distributed in the Atlantic and Indo-West Pacific oceans. Gennadas brevirostris is restricted to the Atlantic and Hepomadus tener occurs in the Western Atlantic and Indo-West Pacific oceans. Bentheogennema intermedia is the only species recorded for the Eastern Pacific. The latitudinal distribution among them ranges between 50°N and 40°S.